Magnetic properties of high purity scandium, yttrium, lanthanum and lutetium and the effects of impurities on these properties (U.S. Atomic Energy Commission ; distributed by the Office of Scientific and Technical Information, U.S. Department of Energy, 1972)
Erbium/Effects On Magnetic Properties Of Scandium;Scandium/Magnetic Properties Of, Effects Of Impurities On;Lanthanum/Magnetic Properties Of, Effects Of Impurities On;Oxygen/Effects On Magnetic Properties Of Scandium, Yttrium, Lanthanum, And Lutetium;Yttrium/Magnetic Properties Of, Effects Of Impurities On;Gadolinium/Effects On Magnetic Properties Of Scandium;Hydrogen/Effects On Magnetic Properties Of Scandium, Yttrium, Lanthanum, And Lutetium;Lutetium/Magnetic Properties Of, Effects Of Impurities On.